TRANSFORMATIONAL- RELIGIOUS LEADERSHIP MODEL IN DEVELOPING LITERACY ACHIEVEMENT - Minarti, Sri; Farhan, Moh.; Aufa, Ari Abi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Among these goals is achieving achievement, because achievement is an indicator of success in achieving an institution. The purpose of this study is to determine the leadership model at MA Islamiyah Senori Tuban by focusing on research on: (1) How the Transformational-Religious Leadership Model in Developing Literacy Achievements and (2) Implementation of the Transformational-Religious Leadership Model in Developing Literacy Achievements. The research method used is a case study qualitative method at MA Islamiyah Senori Tuban. Techniques used in data collection through direct observation, interviews with several informants, and documentation, the analysis of researchers using data reduction, data presentation, interpretation and drawing conclusions. Aspects of transformational-religious leadership include ideal influences, inspirational motivation, intellectual stimulation, considerations based on the individual. Meanwhile, the principles of transformational-religious leadership include building awareness and organizational responsibility. Characteristics include having charisma, individual consideration, intellectual stimulation. Religious includes honesty, discipline, humility, usefulness, and others. Implementation is realized in the form of a Literacy Program in the form of Prodistics (applied fields), Final work in the form of books, Passion for libraries, skimming, procurement of reading parks.